Endophytic fungus Phomopsis sp. as a source of 3-nitropropionic acid with larvicidal activity against Aedes aegypti (Linnaeus 1762, Diptera: Culicidae) - Garcia, Armando da Costa; Júnior, Orivaldo Teixeira de Menezes; Mariano, Lissa Apolonia; Santiago, Letícia Corrêa; Araújo, Ângela Regina [UNESP]; Monfardini, Julia Dietsche [UNESP]; Simões, Rejane de Castro; de Oliveira, André Correa; Roque, Rosemary Aparecida; Tadei, Wanderli Pedro; Teles, Helder Lopes; de Oliveira, Camila Martins (FapUNIFESP (SciELO), 2022)
Background: Aedes aegypti is the primary vector of viruses, such as Zika, chikungunya, yellow fever, and dengue. In this context, a biomonitored chemical study was conducted to evaluate the activity of the crude extract of the endophytic fungus Phomopsis sp. against the larvae of Aedes aegypti. Methods: Crude extract, fractions, and isolated substances were evaluated in in-vitro assays against third-stage larvae of Aedes aegypti. Results: We isolated 3-nitropropionic acid with an LC50 of 15.172 ppm and LC90 of 18.178 ppm after 24 hours of larval exposure. Conclusions: The results indicated that 3-nitropropionic acid exerted larvicidal activity.
Keywords: Biomonitored chemical; Dengue; Secondary metabolite